2015
DOI: 10.1007/s00467-015-3059-9
|View full text |Cite
|
Sign up to set email alerts
|

The vascular phenotype of children with systemic lupus erythematosus

Abstract: This study shows that our patients with JSLE had increased cIMT without an increase in PWV, suggesting possible early adaptive changes in JSLE. Follow-up data are needed to determine whether these changes result in clinically significant CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In addition, the study of Yildiz et al 34 found higher aortic PWV in 24 premenopausal women with SLE compared with 24 age- and sex-matched controls. However, both the study by Tziomalos et al 16 (including 55 patients with SLE and 61 controls) and the study by Quinlan et al 30 (including 45 patients with SLE and 40 controls) found that PWV did not differ between patients with SLE and controls.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, the study of Yildiz et al 34 found higher aortic PWV in 24 premenopausal women with SLE compared with 24 age- and sex-matched controls. However, both the study by Tziomalos et al 16 (including 55 patients with SLE and 61 controls) and the study by Quinlan et al 30 (including 45 patients with SLE and 40 controls) found that PWV did not differ between patients with SLE and controls.…”
Section: Discussionmentioning
confidence: 89%
“…The basic characteristics of the selected studies are summarized in Table 1. [16][17][18][19][25][26][27][28][29][30][31][32][33][34] In 9 studies, patients were diagnosed with SLE by the American College of Rheumatology (ACR) classification criteria, whereas the other 5 studies did not mention the diagnostic criteria. The age, sex, and BMI were matched between patients with SLE and controls in each included study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…left ventricular hypertrophy, increased carotid artery intima-media thickness, and pulse wave velocity) despite relatively short disease duration. 2830…”
Section: Discussionmentioning
confidence: 99%
“…JSLE has an increased CVD and mortality risk compared to adult-onset SLE [ 12 , 125 , 126 ]. Investigating the development of atherosclerosis and CVD in these younger, more severely affected patients, has potential clinical value in identifying early mechanisms of vascular damage and biomarkers to guide management strategies [ 114 ]. Whilst traditional risk factors such as hypertension, diabetes and high cholesterol contribute to the increased cardiovascular risk (CVR) in SLE overall, they fail to fully account for it [ 127 ].…”
Section: Renal Biomarkersmentioning
confidence: 99%
“…Whilst traditional risk factors such as hypertension, diabetes and high cholesterol contribute to the increased cardiovascular risk (CVR) in SLE overall, they fail to fully account for it [ 127 ]. Ideally, all patients with SLE should receive monitoring and treatment for modifiable CVR factors [ 114 , 126 ]. The interplay between traditional CVR factors, increased disease associated inflammation and treatment burden in these younger patients could contribute to early, accelerated atherosclerosis in JSLE [ 125 , 127 , 128 ].…”
Section: Renal Biomarkersmentioning
confidence: 99%